Great Northern Beans (Phaseolus vulgaris L.) Lower Cholesterol in Hamsters Fed a High-Saturated-Fat Diet - Nguyễn, Tiến An (2023)
Dietary interventions for high cholesterol, a primary risk factor for cardiovascular disease, are generally considered before prescribing drugs.